Evolution of the Alx homeobox gene family: parallel retention and independent loss of the vertebrate Alx3 gene. - McGonnell, I; Graham, A; Richardson, J; Fish, J; Depew, M; Dee, C; Holland, P; Takahashi, T (2011)
The Alx gene family is implicated in craniofacial development and comprises two to four homeobox genes in each vertebrate genome analyzed. Using phylogenetics and comparative genomics, we show that the common ancestor of jawed vertebrates had three Alx genes descendent from the two-round genome duplications (Alx1, Alx3, Alx4), compared with a single amphioxus gene. Later in evolution one of the paralogues, Alx3, was lost independently from at least three different vertebrate lineages, whereas Alx1 and Alx4 were consistently retained. Comparison of spatial gene expression patterns reveals that the three mouse genes have equivalent craniofacial expression to the two chick and frog genes, suggesting that redundancy compensated for gene loss. We suggest that multiple independent loss of one Alx gene was predisposed by extensive and persistent overlap in gene expression between Alx paralogues. Even so, it is unclear whether it was coincidence or evolutionary bias that resulted in the same Alx gene being lost on each occasion, rather than different members of the gene family.